A new simulated annealing algorithm for simultaneous open-pit and waste dump scheduling in mining complexes - Jingsi Lin; Mohammad Waqar Ali Asad; Erkan Topal; Ping Chang (PLoS ONE, 2025)
Production scheduling models for open-pit mining complexes determine the optimal sequence for extracting mining blocks while adhering to technical and operational constraints. Although various mathematical models are available in the literature, solving them for large-scale operations remains computationally intensive. This challenge becomes more complex when models aim to simultaneously schedule block extraction and waste dumping, as this introduces additional variables and constraints, further complicating the problem. This paper presents a novel Simulated Annealing (SA)-based algorithm as a solution method for the simultaneous optimisation of block extraction and waste dumping sequences in open-pit mining complexes. The proposed approach incorporates an innovative variable reduction technique and a heuristic for generating reliable initial solutions. Numerical results show that the proposed algorithm achieves an NPV within 6.08% of the exact solution derived through a commercial solver while reducing the runtime by 82%. More importantly, for relatively larger instances that commercial solver fails to resolve, the proposed method maintains robust performance and delivers high-quality solutions within reasonable computational times.